Comparisin of Alternative Methods for the Control of Experimental Error in Perrenial Crops - Seena C (Department of Agricultural Statistics, College of Horticulture, 1994)
The feasibility of using certain novel devices for the control of error in experiments on perennial crops was examined on the basis of actual experimental data and the resulting efficiency gain evaluated.